Predictors of Immunization Defaulting among Children Age 12-23 Months in Hawassa Zuria District of Southern Ethiopia: Community Based Unmatched Case Control Study - Fikru Tesfaye; Alemu Tamiso; Yemane Birhan; Tariku Tadele (Intelektual Pustaka Media Utama, 2014)
As part of the overall package of maternal and child health services in Ethiopia, all children are provided with free immunization services and it is available in all government health facilities, both in rural and urban areas. But significant number of children was defaulted from Immunization schedule, even after the health extension program was launched. Therefore, the study was assessed predictors of immunization defaulting among children age range of 12-23 months, in Hawassa Zuria district of southern Ethiopia. Unmatched case control study was conducted in six Kebeles which were selected from 26 kebeles by simple random sampling techniques. Cases were children in the age ranges of 12 - 23 months who did not complete the recommended immunization. All cases (105) and controls (209) in the kebeles were identified by using health posts Vaccine registration book. Bivariable and multiple logistic regression model were used to identify important predictor of immunization defaulting. P-value of less than 0.05 was considered as the level of significances. The study identified educational status, place of delivery, immunization related knowledge, ANC follow up and household wealth status as significant predictors of defaulting from immunization schedules. Sustained health education on vaccination related knowledge and institutional delivery services utilization will be needed. The household literacy and economic status should also get emphasis so as to decreases defaulting of children from immunization schedule.